THE SYSTEMATIC REVIEW OF LAPAROSCOPIC SURGERY FOR TRAUMA - Aprialdi, Bimayudo; Sultan Alauddinsyah, Teuku; Takhta Alfina, Fitria; Rohmatika Arum Dhati, Melinda (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: While trauma is the primary cause for mortality during the early half of a person's life, it ranks as the fourth greatest reason fatalities in the general population. When performed by skilled surgeons under hemodynamically stable circumstances, laparoscopy proves as being secure and efficient procedure for managing patients with abdominal trauma. Methods: Under evaluating it against the criteria established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, the present research demonstrated that it satisfied all of the criteria. As a result, the professionals ensured that the study was as current as feasible. The aforementioned search technique considered papers published during 2013 through 2023. Multiple electronic reference sources, including Pubmed as well as SagePub, were employed to accomplish it. It was decided not to consider evaluation parts, productions those were previously released, as well as projects which had been just partly done. Result: Our search yielded 4570 papers within the PubMed database, but only 616 articles in SagePub. The search outcomes for the last year of 2014 generated an overall of 60 PubMed publications and 46 SagePub publications. At the final phase, our team gathered an entire collection of four publications, three from PubMed and one from SagePub. He selected four studies that satisfied the requirements. Conclusion: In summary, laparoscopic surgery is an acceptable substitute for open surgery; nonetheless, the procedure should only be carried out by skilled surgeons in state-of-the-art medical facilities. More carefully planned RCTs are need to confirm the effectiveness of laparoscopy as the detection and management of abdominal trauma.